2020
DOI: 10.1186/s40798-020-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Human Activity Recognition System for Ballet Tasks

Abstract: Background: Accurate and detailed measurement of a dancer's training volume is a key requirement to understanding the relationship between a dancer's pain and training volume. Currently, no system capable of quantifying a dancer's training volume, with respect to specific movement activities, exists. The application of machine learning models to wearable sensor data for human activity recognition in sport has previously been applied to cricket, tennis and rugby. Thus, the purpose of this study was to develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Usually, the accuracy of HAR algorithms reduces for finer levels of classification as predictions become more complex. Our results are consistent with these previous studies, where reductions in accuracy for subsequent level classification have been reported to range between 4.2% and 16.4% [ 20 , 24 ]. While we compared the results of our models to previous HAR literature, the considerable heterogeneity between these studies reduces the capacity to make meaningful comparisons [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Usually, the accuracy of HAR algorithms reduces for finer levels of classification as predictions become more complex. Our results are consistent with these previous studies, where reductions in accuracy for subsequent level classification have been reported to range between 4.2% and 16.4% [ 20 , 24 ]. While we compared the results of our models to previous HAR literature, the considerable heterogeneity between these studies reduces the capacity to make meaningful comparisons [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, deep learning approaches like CNN are able to handle nonlinear interactions between features, something which is limited when using traditional machine learning approaches where features are defined by the researcher. There are many laboratory studies that have reported the accuracy of classifying physical activities from IMU data [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] using both traditional and deep learning approaches. Ramanujam et al [ 28 ] provide a review of the most up-to-date computational advances in deep learning for HAR which is beyond the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al [20] obtained an accuracy of 0.959 in the recognition of specific gym exercises such as bench dips using both accelerometer and gyroscope. More recently, the team of Hendry et al [25] proposed an activity recognition system using 6 sensors to detect simple key movements (jumping and leg lifting) in ballet with the help of a convolutional neural network (CNN) achieving an accuracy of 0.982. Another research team [26] investigated the recognition 10 cross-fit specific exercises based on a deep learning approach (CNN) and reached an impressive recognition rate of more than 99.9 %.…”
Section: Related Workmentioning
confidence: 99%
“…A large number of researchers have been attracted to human action classification problem due to its wide range of real-world applications. The notable implementations cover visual surveillance [1], smart homes [2], sports [3], entertainment [4], healthcare monitoring [5], patient monitoring [6], elderly care [7], Virtual-Reality [8], human-computer interaction [9], and so on.…”
Section: Introductionmentioning
confidence: 99%